EXPLORATION OF SEMANTICS AND SHADES OF ASSOCIATIVE MEANING - Nwokwu, Ndidi Theophilus (EBSU Journal of Social Sciences and Humanities, 2023)
Semantics studies the meaning of words and sentence in language. It is necessary to mention that Semantics has not enjoyed a prominent position in linguistics until very recently. Several reasons have been proposed for this neglect. One of the reasons is attributed to the nature of meaning itself. Meaning is not a suitable phenomenon. An expression can be possible of a number of interpretations depending on the speakers –hearer or context. So, a phenomenon which is as elusive as meaning cannot be easily investigated with some degree of objectivity. This work looks at the concept of meaning, the mentalist view of meaning bringing insight to the associative meaning and its subdivisions.